Design of Online Ticket Information System on Ara Garden Tour in Bahtera Makmur Village - Miranda, Reza Aditya (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2023)
Has several interesting tours, one of which is Ara Garden Tourism, a place in the form of an artificial tourist park located in Bagan Batu, Riau, Bagan Sinembah District, Rokan Hilir Regency. However, ticket purchases can only be made by buying directly on the spot when entering the tourist spot. This can make it difficult to order tickets because of the large number of visitors. So here the e-ticket application design will be made using the RAD method to analyze and design applications for online ticket booking at Ara Garden Tourism. In this design using dart and fluter programming languages as application development, using VCS (Microsoft Visual Studio Code) as a code editor in creating the application. Therefore I use a database that functions to store and manage data through SQL commands or queries, applications that have more complex data processing are postgreSQL. The Ara Garden tourist ticket application has been created and the prototype of the application was tested by sending a questionnaire to 20 respondents with an average score of 4.021 and most of the responses from potential users said that the ticket prototype was easy to understand and use. So here we will try to create an e-ticket application design. E-tickets can make it easier for buyers or visitors to get them because they don't need to come directly to the tourist attraction.